Lung recruitment in the prone position after cardiac surgery: a randomised controlled study - Martinsson, Andreas; Houltz, Erik; Wallinder, Andreas; Lindgren, Sophie; Thorén, Anders (British journal of anaesthesia : BJA, 2021)
Atelectasis after cardiac surgery is common and promotes ventilation/perfusion mismatch, infection, and delayed discharge from critical care. Recruitment manoeuvres are often performed to reduce atelectasis. In severe respiratory failure, recruitment manoeuvres in the prone position may increase oxygenation, survival, or both. We compared the effects of recruitment manoeuvres in the prone vs supine position on lung aeration and oxygenation in cardiac surgical patients. Subjects were randomised to recruitment manoeuvres (40 cm H2O peak inspiratory pressure and 20 cm H2O PEEP for 30 s) in either the prone or supine position after uncomplicated cardiac surgery. The co-primary endpoints were lung aeration (end-expiratory lung volume measured by electrical impedance tomography (arbitrary units [a.u.]) and lung oxygenation (ratio of arterial oxygen partial pressure to fractional inspired oxygen [Pao2/FiO2 ratio]). Secondary outcomes included postoperative oxygen requirement and adverse events. Thirty subjects (27% female; age, 48–81 yr) were recruited. Dorsal lung tidal volume was higher after prone recruitment manoeuvres (363 a.u.; 95% confidence intervals [CI], 283–443; n=15) after extubation, compared with supine recruitment manoeuvres (212 a.u.; 95% CI, 170–254; n=15; P<0.001). Prone recruitment manoeuvres increased dorsal end-expiratory lung volume by 724 a.u. (95% CI, 456–992) after extubation, compared with 163 a.u. decrease (95% CI, 73–252) after supine recruitment manoeuvres (P<0.001). The Pao2/FiO2 ratio after extubation was higher after prone recruitment manoeuvres (46.6; 95% CI, 40.7–53.0) compared with supine recruitment manoeuvres (39.3; 95% CI, 34.8–43.8; P=0.04). Oxygen therapy after extubation was shorter after prone (33 h [13]) vs supine recruitment manoeuvres (52 h [22]; P=0.01). No adverse events occurred. Recruitment manoeuvres in the prone position after cardiac surgery improve lung aeration and oxygenation. NCT03009331.